Effect of low-density lipoproteins and trehalose on the quality of cryopreserved bovine semen - Elizabeth Varela-Giraldo (Universidad de Antioquia, 2020)
Background: In artificial insemination, chicken egg yolk is added to bovine semen to protect it during the cryopreservation process, although it contains substances that can affect the microbiological quality and metabolism of sperm. Objective: To evaluate post-thaw quality of bovine cryopreserved semen added with centrifuged and non-centrifuged egg yolk, low-density lipoproteins (LDL), and trehalose (T). Methods: Ten ejaculates from five bulls were cryopreserved under the treatments T1: pure egg yolk (PEY) at 20% v/v, T2: centrifuged egg yolk (CEY) at 20% v/v, T3: LDL at 8% v/v, T4: T at 100 mM, and T5: T at 100 mM plus LDL at 8% v/v (TLDL). Spermatic motility and kinetics, functional membrane integrity (FMI), structural membrane integrity (SMI), sperm vitality (SV) and abnormal morphology (AM) were assessed using the Sperm Class Analyzer (SCA®) system, hypoosmotic test (HOST), SYBR/PI probes, and eosin–nigrosin staining, respectively. A completely randomized design was used. Normal distribution of the variables was validated through the Kolmogórov– Smirnov test. A generalized linear model was used to determine sources of variation. Means were compared using the Tukey test. Results: Inclusion of CEY or LDL had a similar effect on sperm protection, and were superior for motility, kinetics and membrane integrity compared to the other treatments (p<0.05). CEY was superior for progressive motility (p<0.05). The cryoprotective action of LDL was similar to TLDL for motility and kinetics, SMI, SV, and AM (p<0.05). Inclusion of PEY and T resulted in the lowest semen quality (p<0.05). The use of T resulted in a reduction in FMI and SMI (p<0.05). No differences in AM between treatments were found (p>0.05). Conclusions: Egg yolk can be replaced by centrifuged egg yolk or low-density lipoproteins in the freezing extender used for bovine semen used in artificial insemination.